INDIAN MUSLIM RESTAURANT DINE OUT FREQUENCY: MALAYSIAN DEMOGRAPHIC PERSPECTIVE - Lim Soon Chow, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Dine-out frequency is the fundamental measure of footfall in a food service eateries. Indian Muslim restaurant (IMR) in Malaysia remains the popular hangout place and food-away-from-home choice among Malaysians. The unique IMR eateries well blended with the culture of Malaysian food, traditions, and Malaysian multicultural society identity. This eaterie is continuing mushrooming around the country and flourish the foodservice industry. Despite, numerous research focusing on success factors, contribution to gastronomic, and management. However, a little study exploring the diners' primary demographic in this highly valued eateries. Therefore, this paper seeks to unveil the basic demographic profile in the IMR sector. The results provide rudimentary diners segmentation insights in the Malaysian context and benefits to a new venture and quantifiable insights to foodservice entrepreneurs.